AN ANALYSIS OF COVID-19 POSTERS SYMBOLS: A SEMIOTIC STUDY (International Conference on Social and Islamic Studies, 2022)
Beginning from the city of Wuhan, exactly in China, this new kind of infection has spread to different areas of the planet causing the development of Covid sickness 2019 or otherwise called COVID-19. Obviously, this condition ought not be trifled with and left alone. Not just inconvenient as far as wellbeing, the Covid enormously affects schooling and economy in the World. The World Health Organization (WHO) has likewise proclaimed a COVID-19 pandemic since March 11, 2020. In the case of the COVID-19 pandemic, this is the first and is caused by the corona virus which has existed since the end of previous years. This study pointed toward investigating Coronavirus posters through semiotic review. This study utilized descriptive technique which 22 posters sent off by WHO utilized as the information source. The researchers applied hypothesis of McGregor to dissect the sort of linguistic sign on the posters. In the wake of leading exploration, the researchers found 11 linguistic sign and 11 non-linguistic sign from the findings.